Protective effects of ?-3 essential fatty acids against formaldehyde-induced neuronal damage in prefrontal cortex of rats - Zararsiz, Ismail; Kus, Ilter; Akpolat, Nusret; Songur, Ahmet; Ogeturk, Murat; Sarsilmaz, Mustafa (Wiley, 2006)
The aim of this study was to examine the neurotoxicity of formaldehyde on prefrontal cortex and the protective effects of omega-3 essential fatty acids against these toxic effects. For this purpose, 21 male Wistar rats were divided into three groups. The rats in group I comprised the controls, while the rats in group 11 were injected every other day with formaldehyde (FA). The rats in group III received omega-3 fatty acids daily while exposed to formaldehyde. At the end of the 14-day experimental period, all rats were killed by decapitation. The brains of the rats were removed and the prefrontal cortex tissues were obtained from all brain specimens. Some of the prefrontal cortex tissue specimens were used for determination of superoxide dismutase (SOD). glutathione peroxidase (GSH-Px), and malondialdehyde (MDA) levels. The remaining prefrontal cortex tissue specimens were used for light microscopic and immunohistochemical evaluation. The levels of SOD and GSH-Px were significantly decreased, and MDA levels were significantly increased in rats treated with formaldehyde compared with those of the controls. Furthermore, in the microscopic examination of this group, formation of apoptotic bodies, pycnotic cells, and apoptotic cells including nuclear fragmentation and membrane budding were observed. However, increased SOD and GSH-Px enzyme activities. and decreased MDA levels were detected in the rats administered w-3 fatty acids while exposed to formaldehyde. Additionally, cellular damage caused by formaldehyde was decreased, and structural appearance was similar to that of the control rats in this group. The biochemical and histological findings observed in all groups were also confirmed by immunohistochemical evaluation. It was determined that formaldehyde-induced neuronal damage in prefrontal cortex was prevented by administration of omega-3 essential fatty acids. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: formaldehyde; omega-3 fatty acids; prefrontal cortex; rat; neurotoxicity